Interpretation of The Setan Card in Tarot Nusantara: A Semiotic Study Based on Roland Barthes - Mulia, Arief Budi; Gustianingsih, Gustianingsih; Lubis, Rosliana (MAN 4 Kota Pekanbaru, 2026)
Tarot cards contain complex symbolic systems, including The Setan (the Devil) card in Tarot Nusantara. This complexity makes Barthes’ semiotics relevant for uncovering deeper meanings through denotation, connotation, and myth. This qualitative descriptive study aims to identify the similarities, differences, strengths, and weaknesses between the researcher’s interpretation (based on Barthes’ semiotic framework) and a tarot practitioner’s interpretation of the Setan card in Tarot Nusantara. The data were analyzed using a commensurate method, a comparative analytical approach used to examine relationships between interpretations. The analysis involved identifying and classifying the key symbolic elements of the card, followed by systematic comparisons to determine similarities, differences, and core meanings between the researcher’s interpretation and that of the tarot practitioner. Both interpretations associate the card with human powerlessness driven by lust and desire, representing the darker aspects of human nature. However, the semiotic analysis reveals that the card also conveys a symbolic message of self-awareness and the potential for liberation from psychological and spiritual attachment. The analysis shows that the researcher’s interpretation focuses on psychological dimensions and the potential for self-transformation, while the practitioner’s interpretation emphasizes external negative consequences and immediate risks.